PLoS Pathogens Issue Image | Vol. 7(1) January 2011 (PLOS Pathogens, 2011)
Herpes viral adaptor protein HSV-1 ICP27 recognizes and specifically binds to the surface of the RRM domain of cellular export factor REF/Aly. The recognition fragment of the ICP27 peptide is shown docked to the binding pocket on the REF RRM, with selected residues labeled. A similar binding surface on REF/Aly is occupied by an adaptor protein from a different herpesvirus, HVS ORF57. The importance of the key amino acid residues within the binding sites of both viral proteins was confirmed by site-directed mutagenesis. Together, these data precisely map amino acid residues responsible for the direct interactions between viral adaptors and cellular REF/Aly and provide the first molecular details of how herpes viruses access the cellular mRNA export pathway (see Tunnicliffe et al., doi:10.1371/journal.ppat.1001244). Image Credit: Richard B. Tunnicliffe and Alexander P. Golovanov, University of Manchester